(untitled) (Research, Society and Development, 2022)
Objective: To identify the fears experienced by nursing professionals during the Covid-19 pandemic. Method: This is an integrative literature review, prepared with articles from the Latin American Caribbean Literature in Health Sciences databases and the Scientific Electronic Library Online, using the descriptors “fear”, “nursing”, and “Covid-19”, combined using the Boolean AND resource in all bases. Results: 17 articles published between 2020 and 2022 were selected. These showed that the main fears were the increased risk of contamination; the shortage of Personal Protective Equipment, and material and human resources; fear of contaminating family members; fear of death of family members; fear of social exclusion, during the fight against Covid-19. Conclusion: In this way, the nursing professionals who worked on the front lines of Covid-19, experienced different fears that could lead the nursing professional to have damage to their mental health, requiring actions that aim to reduce this damage.